RESPITE: switching to riociguat in pulmonary arterial hypertension patients with inadequate response to phosphodiesterase-5 inhibitors - Hoeper, Marius M; Simonneau, Gérald; Corris, Paul A; Ghofrani, Hossein-Ardeschir; Klinger, James R; Langleben, David; Naeije, Robert; Jansa, Pavel; Rosenkranz, Stephan; Scelsi, Laura; Grünig, Ekkehard; Vizza, Carmine Dario; et al. (The European respiratory journal, 2017)
A proportion of pulmonary arterial hypertension (PAH) patients do not reach treatment goals with phosphodiesterase-5 inhibitors (PDE5i). RESPITE investigated the safety, feasibility and benefit of switching from PDE5i to riociguat in these patients.RESPITE was a 24-week, open-label, multicentre, uncontrolled study. Patients in World Health Organization (WHO) functional class (FC) III, with 6-min walking distance (6MWD) 165-440 m, cardiac index <3.0 L·min-1·m-2 and pulmonary vascular resistance >400 dyn·s·cm-5 underwent a 1-3 day PDE5i treatment-free period before receiving riociguat adjusted up to 2.5 mg maximum t.i.d Exploratory end-points included change in 6MWD, WHO FC, N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and safety.Of 61 patients enrolled, 51 (84%) completed RESPITE. 50 (82%) were receiving concomitant endothelin receptor antagonists. At week 24, mean±sd 6MWD had increased by 31±63 m, NT-proBNP decreased by 347±1235 pg·mL-1 and WHO FC improved in 28 patients (54%). 32 patients (52%) experienced study drug-related adverse events and 10 (16%) experienced serious adverse events (2 (3%) study drug-related, none during the PDE5i treatment-free period). Six patients (10%) experienced clinical worsening, including death in two (not study drug-related).In conclusion, selected patients with PAH may benefit from switching from PDE5i to riociguat, but this strategy needs to be further studied.
Keywords: dospělí; Severní Amerika; North America; Prospective Studies; Humans; Natriuretic Peptide, Brain; lidé středního věku; prospektivní studie; Europe; Middle Aged; Young Adult; Antihypertensive Agents; mladý dospělý; plicní hypertenze; Pyrimidines; Světová zdravotnická organizace; test chůzí; antagonisté endotelinového receptoru; Peptide Fragments; inhibitory fosfodiesterasy 5; mužské pohlaví; Endothelin Receptor Antagonists; Severity of Illness Index; stupeň závažnosti nemoci; Adult; pyrimidiny; Phosphodiesterase 5 Inhibitors; natriuretický peptid typu B; Adolescent; antihypertenziva; Hypertension, Pulmonary; výsledek terapie; Evropa; Walk Test; peptidové fragmenty; Treatment Outcome; ženské pohlaví; World Health Organization; lidé; mladiství; Pyrazoles; cévní rezistence; Aged; senioři; Male; pyrazoly; Vascular Resistance; Female